Planning Public Space Climate Comfortability: A GIS-Based Algorithm for the Compact Cities of the Far North - Anna Korobeinikova; Nina Danilina; Irina Teplova (Land)
The issue of forming a comfortable environment in cities with complex climatic conditions has always been an urgent and difficult issue for urban planners. Cities located in the territories of the Far North are characterized by extremely harsh climatic characteristics that affect the planning solutions for the public spaces of the city. Low temperatures and strong winds reduce the time of comfortable stay in the open air, which leads to a decrease in the mobility of the population in the city and stimulates the use of personal cars. The research question is the rational placement of points of interest on the street network to ensure a comfortable travel time between objects. The research methodology of public space planning taking into account the climatic comfortability of Far North cities is proposed in this article. Also, an automated GIS-based algorithm for determining intermediate points on linear objects to increase POIs’ connectivity for the development of the public space of Far North cities under the condition of organizing climatic comfort is proposed. Development of safe and comfortable public space on the basis of network accessibility, taking into account the difficult climatic conditions of these cities, will increase the social activity of the population and tourists, as well as promote economic growth and business development in the city.